Policy Model For The Development of Community-Based Tourism Destinations in Banggai Laut Regency - Fadli Sandewa; Asna Aneta; Yowan Tamu; Sukarman Kamuli; Yanti Aneta (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This study aims to develop a policy model for community-based tourism destination development in Banggai Laut Regency, where tourism's contribution remains suboptimal despite significant potential. The research questions focus on the ongoing implementation of tourism policies and the role of local communities in sustainable tourism. Employing a qualitative method with a phenomenological approach, data was collected through observation, interviews, and documentation from key stakeholders. The findings reveal that current models lack effective integration of local communities, leading the study to propose the "Community-Governed Destination Development" model. This model contributes academically by repositioning local communities as primary decision-makers, emphasizing participatory governance and local wisdom for inclusive sustainability.